Performance Effectiveness of the Land Agency in Issuing Land Rights Certificates and its Impact on Regional Income Banjarbaru City - Adwin Tista; Ahmad Yunani; Noor Rahmini (International Journal Labs, 2026)
The research aims to determine the effectiveness of the performance of the Banjarbaru city land agency in issuing land rights certificates; know the supporting and inhibiting factors; knowing the impact on regional income of the city of Banjarbaru and efforts to increase the effectiveness of the performance of the land agency of the city of Banjarbaru in issuing certificates of land rights. The research method was an analytical descriptive method with a qualitative descriptive approach. The research model is Geertz Interpretive namely the approach by looking for